Improved Antiglioblastoma Activity and BBB Permeability by Conjugation of Paclitaxel to a Cell‐Penetrative MMP‐2‐Cleavable Peptide. Issue 3 (21st December 2020) - Hua, Dan; Tang, Lida; Wang, Weiting; Tang, Shengan; Yu, Lin; Zhou, Xuexia; Wang, Qian; Sun, Cuiyun; Shi, Cuijuan; Luo, Wenjun; Jiang, Zhendong; Li, Huining; et al.
Abstract: In order to solve the problems of receptor promiscuity and poor blood‐brain barrier (BBB) penetration in the treatment of glioblastomas (GBM), a novel dual‐functional nanocomplex drug delivery system is developed based on the strategy of peptide‐drug conjugates. In this study, SynB3‐PVGLIG‐PTX is designed and screened out by matrix metalloproteinase‐2 (MMP‐2), to which it exhibits the best affinity. The MMP‐2‐sensitive peptide (PVGLIG) and a cell‐penetration peptide (SynB3) are combined to form a dual‐functional peptide. Moreover, as a drug‐peptide nanocomplex, SynB3‐PVGLIG‐PTX exhibited a high potential to form an aggregation with good solubility that can release paclitaxel (PTX) through the cleavage of MMP‐2. From a functional perspective, it is found that SynB3‐PVGLIG‐PTX can specifically inhibit the proliferation, migration, and invasion of GBM cells in vitro in the presence of MMP‐2, in contrast to that observed in MMP‐2 siRNA transfected cells. Further investigation in vivo shows that SynB3‐PVGLIG‐PTX easily enters the brain of U87MG xenograft nude mice and can generate a better suppressive effect on GBM through a controlled release of PTX from SynB3‐PVGLIG‐PTX compared with PTX and temozolomide. Thus, it is proposed that SynB3‐PVGLIG‐PTX can be used as a novel drug‐loading delivery system to treat GBM due to its specificity and BBB permeability. Abstract : SynB3‐PVGLIG‐PTX exhibits a strong affinity with MMP‐2, and it can enhance water solubility by agglomerating to form a special structure with a positive charge; a controlled release of PTX from SynB3‐PVGLIG‐PTX occurs upon cleavage of MMP‐2, implying that SynB3‐PVGLIG‐PTX has a specific cytotoxicity in GBM cells; SynB3‐PVGLIG‐PTX can effectively inhibit GBM in vitro and in vivo.